Atypical acquired melanocytic nevus in a girl with epidermolysis bullosa type Dowling-Meara. - Bonifazi, E.; Annicchiarico, G. (European Journal of Pediatric Dermatology, 2009)
The subjects with epidermolysis bullosa do not present an increased number of melanocytic nevi. However, some of these nevi, arisen on the residua of previous blisters, are characterized by rapid growth, which can lead in a few months to the size of several centimeters, by irregular asymmetrical borders and by a peculiar shape consisting of numerous isolated elements reminiscent of satellites (1). These nevi, usually forming between 6 and 18 years (1), then remaining stable with time or possibly spontaneously regressing (2), should not be removed (3). When they are removed, due to esthetical reasons, as in the case here reported, or to scarce knowledge of their benign nature, the histologic examination shows the structure of a common melanocytic nevus.